Phenolic Composition and Bioactivities of Invasive Ailanthus altissima (Mill.) Swingle Leaf Extracts Obtained by Two-Step Sequential Extraction - Maria Denisa Cocîrlea; Amalia Soare; Anca Roxana Petrovici; Mihaela Silion; Teodora Călin; Simona Oancea (MDPI AG, 2024)
Ailanthus altissima, a highly invasive species, contains valuable compounds in different plant parts, indicating great practical potential. This paper proposes the use of non-polar (n-hexane) and polar (ethanol) solvents for the extraction of antioxidant compounds from A. altissima (family Simaroubaceae) leaves in a sequential two-step process. Fresh and dried leaves were examined for their microstructure by scanning electron microscopy, and for color changes in the CIELAB color space co-ordinates. An investigation of the harvesting season, processing (freezing and drying), and solvent indicates ethanol can be used for the highly efficient extraction of phenolics, flavonoids, tannins, and carotenoids. Statistically significant differences were found between the autumn and summer samples for phenolic content, and between dried and frozen samples for tannin content. The HPLC phenolic profile indicates more phenolics (nine polyphenols) in dried leaves harvested in both seasons compared to those in frozen ones (five to six polyphenols). Frozen leaves showed a higher antioxidant activity in a ferric-reducing antioxidant power assay than that of the dried samples, which exhibited a higher antioxidant activity using the 1, 1-diphenyl-2-picryl-hydrazyl assay, but it was not statistically significant. The phenolic, flavonoid, and carotenoid contents significantly influenced the antioxidant activities. Among the ethanolic extracts, those from dried leaves showed better antibacterial activity, in particular, on Staphylococcus aureus and Enterococcus faecalis. The high bioactive content and activity of A. altissima leaves make them suitable natural raw materials for various applications.